2016
DOI: 10.3389/fpls.2016.01963
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome B Negatively Affects Cold Tolerance by Regulating OsDREB1 Gene Expression through Phytochrome Interacting Factor-Like Protein OsPIL16 in Rice

Abstract: Cross talk between light signaling and cold signaling has been elucidated in the model plant Arabidopsis and tomato, but little is known about their relationship in rice. Here, we report that phytochrome B (phyB) mutants exhibit improved cold tolerance compared with wild type (WT) rice (Oryza sativa L. cv. Nipponbare). The phyB mutants had a lower electrolyte leakage index and malondialdehyde concentration than the WT, suggesting that they had greater cell membrane integrity and less lipid peroxidation. Real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 53 publications
(82 reference statements)
4
55
0
Order By: Relevance
“…PhyB negatively regulates chloroplast structural stability by lowering levels of unsaturated fatty acids present in membrane lipids . PhyB deficiency positively regulates OsPIL16 and OsDREB1 , thereby alleviating chilling‐induced photoinhibition and enhancing chilling tolerance . Similar mechanisms have also been characterized in Suaeda salsa .…”
Section: Temperature Changesmentioning
confidence: 67%
“…PhyB negatively regulates chloroplast structural stability by lowering levels of unsaturated fatty acids present in membrane lipids . PhyB deficiency positively regulates OsPIL16 and OsDREB1 , thereby alleviating chilling‐induced photoinhibition and enhancing chilling tolerance . Similar mechanisms have also been characterized in Suaeda salsa .…”
Section: Temperature Changesmentioning
confidence: 67%
“…In rice, phyB mutants exhibit enhanced chilling tolerance. A recent study established that OsPIL16 positively regulates expression of OsDREB1 , which could enhance cell membrane integrity and reduce malondialdehyde concentration in these phyB mutants (He et al ). It was also reported that phyB interacts with phytochrome‐interacting factor 4 (PIF4) and PIF7 to repress expression of the CBF pathway and freezing tolerance under long‐day (LD) conditions.…”
Section: Cold Signal Perceptionmentioning
confidence: 99%
“…Transcription factors regulate gene expression by binding to their promoters, thereby promoting or inhibiting their subsequent transcription. A previous study revealed that PIF3 binds to the Gbox (CACGTG) or PBE-box (CACATG), while OsPIF14 and OsPIL16 bind to the N-box [CACG(C/A)G] (Cordeiro et al, 2016;He et al, 2016;Zhang et al, 2013). Based on these findings, an electrophoresis mobility shift assay (EMSA) was performed to identify the specific DNA sequences to which OsPIL15 binds.…”
Section: Ospil15 Directly Targets Ospup7mentioning
confidence: 99%